Antioxidant, analgesic and CNS depressant effects of Synedrella nodiflora - Nahar, Laizuman; Zahan, Ronok; Ibn Morshed, Mahmud Tareq; Haque, Anamul; Alam, Zahangir; Mosaddik, Ashik (© 2012 Elsevier Ltd., 2016)
This article was published in Pharmacognosy Journal [© 2012 Elsevier Ltd.] and the definite version is available at http://www.sciencedirect.com/science/article/pii/S0975357512800824 The article website is at: http://www.sciencedirect.com/science/journal/09753575/4